Automated wrapping machine / Ammar Arham - Arham, Ammar (2023)
The wrapping process of the products at Jalen Sdn Bhd factory were processed manually, which is their worker will hold the wrapper and move around the cartons of products to wrap the product one by one. Limitations occurs when the product produced excessively, because it will consume much time and energy to wrap a lot of products without an automated machine. The main objectives of this project are to develop a machine that reduce manpower for wrapping process and to minimize wrapping time. This project consists of designing, measuring, cutting, drilling, joining, support attachment, combining wrapping and body parts, testing and improvising. As a result, this machine can easily move to another pallet and finish wrap a pallet of products faster than we wrap products on pallet manually. The time taken to wrap full products manually is 1minutes, meanwhile time taken to wrap full products with the machine is 0.3 minutes. In conclusion, the objectives for this project achieve successfully as the time saving of 0.7minutes between manual wrap and automatic wrap process, also the machine is easily used to wrap products on pallet